PENGARUH MODEL PEMBELAJARAN KONSTRUKTIVISME BERBASIS PENGETAHUAN PROSEDURAL TERHADAP PEMAHAMAN SISWA PADA MATA PELAJARAN IPA KELAS IV MI NW REKAT LAUK - Lestarini, Yuniar; Elin, Elin (Cocos Bio, 2022)
This research is purpose to know the preschool model of learningconstructivisme based on the procedural knowledge of the studentsunderstanding in the class IV MI NW Rekat Lauk school. This kind of study isresearch experiment with research design using of one group pretest posttestdesign. Population in this study was a whole class IV of an average of 17people. Data collection technique use a multiple choice tes to there are 25 ofthem. Before data analysis, instruments tested the validity and revalidate. Afterdata accumulate , than analyze the pretest and posttest result. Test result on thepretest averaged 40,91 or in a category less and than when the posttest reachesan average of 76,41 in a fine category. An increase that occurs in studentsunderstanding of preettest to posttest showing an increase by 35%. Dataprerequisite test results with a data normal test with a chi-quadrat, while ahypothetical test technique uses test t- test analysis. The results of thehypothesis test ( t-hitung ˃ t- table ) . this means than an acceptable hypothesisis a significant effect on students understanding of using the green plants mediaon the class IV MI NW Rekat Lauk in the shool.